Prognostic Significance of Thrombocytosis in Patients with Locally Advanced Cervical Carcinoma Treated with Chemoradiotherapy - Sunkappa Dayashankara, Shamsundar; Ramanand, Nanda; Katke, Aradhana; Boraiah, Thejaswini (Reports of Radiotherapy and Oncology, 2019)
Background: The outcome of chemoradiotherapy in patients with locally advanced cervical carcinoma is highly variable and depends on various prognostic factors. Objectives: The aim of this study is to evaluate the prevalence and prognostic significance of thrombocytosis in this group of the patients referred to our institution. Methods: Between January 2008 and December 2012, 195 patients with locally advanced cervical carcinoma (International Federation of Gynecology and Obstetrics (FIGO) stages of IIB-IIIB), treated with external beam radiotherapy (EBRT) to a dose of 45 Gy in 25 fractions along with concurrent chemotherapy (cisplatin 40 mg/m2), followed by HDR brachytherapy EQD2 of 30 Gy. The platelet counts were recorded pre-treatment and during treatment in all the patients. Results: Among the 195 patients, 101 (51.5%) belonged to stage IIB and 94 (48.5%) to stage IIIB. Thrombocytosis (platelet count > 400 × 109/liter) was seen in 31 (15.8%) patients. The overall survival in thrombocytosis group is 41%, which is significantly less than the overall survival of the non-thrombocytosis group, which is 62%. Conclusions: Thrombocytosis is not a frequent finding in patients with locally advanced cervical carcinoma in our population; however, when it is present, it is associated with poor outcome in terms of survival.